Needs Analysis : Development Of Physics Lkpd Based On Problem Based Learning To Facilitate Critical Thinking Skills Of Senior High School Students - Nopi Oktaviya (Physics Learning and Education, 2024)
The 21st century requires critical thinking skills. Physics learning in class XI has not been well implemented due to the lack of critical thinking skills in students. the lack of critical thinking skills in students, to overcome the problems of researchers using the PBL model which aims as follows: 1) testing the use of LKPD based on PBL to improve critical thinking skills to solve problems. Researchers used quantitative research assisted by observation and interviews. The population used was all 11th grade high school students. The research obtained the following findings as follows: 1) students’ critical thinking skills are low when solving physics difficulties using LKPD and PBL learning model. Physics difficulties by using LKPD and PBL learning model; 2) the learning method in the teaching materials is less able to stimulate critical thinking skills. learning methods on teaching materials are less able to stimulate critical thinking skills in solving problems; 3) educators need media solving problems; 3) educators need learning media in the form of LKPD as an alternative for students in mastering critical thinking skills. as an alternative for students in mastering the ability to think critically in solving problems; 3) educators need learning media in the form of LKPD as an alternative to problem solving